A study of lead service lines in California. Issue 9 (23rd August 2022) - Kimbrough, David Eugene
Abstract: Under new regulations In the USA, all Community Water Systems (CWS) need to develop an inventory of their lead service lines (LSL) and determine those owned by their customers. This study will present an approach to address this issue that meets both the letter and the spirit of the law but is also practical and affordable. The first part examines the results of a survey of service lines conducted in California. Eleven million CWS-owned service lines were inventoried, but only four were LSL. The second part of the study was to examine the how California effectively outlawed LSL through the use of plumbing codes. The third part of the study was to determine if these codes had been as effectively implemented on the customer's service lines by examining the customer's service lines in Pasadena. No LSL were found. HIGHLIGHTS: Field study of 108 customer service lines. Review of plumbing codes back to 1880. Survey of 11 million utility service lines. California' ban on lead plumbing. No lead service lines found.